Measuring functioning and disability after a disaster: Results from the typhoon Haiyan/Yolanda-affected areas of the Philippines - Leonardi, Matilde (Animo Repository, 2016)
The most commonly reported data after natural disasters are the number of deceased and displaced and the structural and economic damage, whereas disability data are often lacking. Our study assessed disability among the survivors of the Haiyan/Yolanda typhoon that struck Philippines in 2013 and is aimed to identify which context-level variables are associated with higher disability. We used a cross-sectional design and administered a household questionnaire, an individual sociodemographic questionnaire, and the WHODAS 2.0 to 1982 adults. Logistic regression analysis was carried out to address the degree to which demographic variables, effects of the typhoon, individual health state, and rural or urban residence were associated with higher disability. Those aged above 65, employed individuals, students, those not living in their households, and those with one or more health condition or rating their own as health moderate or very poor had higher likelihood of having severe disability. Survivors living in rural contexts and those who received tools/materials to repair their houses were less likely to have higher disability. This study outlines that disability can and should be used as an indicator in surveys after emergencies to identify the most vulnerable groups, thus guiding policies, reconstruction strategies, and health and social interventions.